Dynamics of theology - Haight, Roger (New York Paulist Press, 1990)
Analyzes the presuppositions, sources, and method of systematic theology and, at the same time, opens up theological imagination to a more creative discipline that can respond to the needs of the world today.
Keywords: Theology